Programmed Adult Kidney Disease: Importance of Fetal Environment - Argeri, Rogério; Thomazini, Fernanda; Lichtenecker, Débora Conte Kimura; Thieme, Karina; do Carmo Franco, Maria; Gomes, Guiomar Nascimento (Frontiers in Physiology, 2020)
The Barker hypothesis strongly supported the influence of fetal environment on the development of chronic diseases in later life. Multiple experimental and human studies have identified that deleterious effect of fetal programming commonly lead to alterations in renal development. The interplay between environmental insults and fetal genome can induce epigenetic changes and lead to alterations in expression of renal phenotype. In this review, we have explored the renal development and its functions, while focusing on the epigenetic findings and functional aspects of the renin-angiotensin system and its components.